2017
DOI: 10.3340/jkns.2016.0202.020
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Glutamate and GABA after High Frequency Subthalamic Stimulation in Parkinsonian Rat

Abstract: ObjectiveHigh frequency stimulation (HFS) of the subthalamic nucleus (STN) is recognized as an effective treatment of advanced Parkinson’s disease. However, the neurochemical basis of its effects remains unknown. The aim of this study is to investigate the effects of STN HFS in intact and 6-hydroxydopamine (6-OHDA)-lesioned hemiparkinsonian rat model on changes of principal neurotransmitters, glutamate, and gamma-aminobutyric acid (GABA) in the striatum.MethodsThe authors examined extracellular glutamate and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…EPN stimulation increased striatal glutamate levels in NL with DBS category and 6-HD with DBS category compared to NL category and 6-HD category, respectively. This result is in accordance with findings of other reports about increased striatal glutamate levels after STN stimulation [ 9 , 11 , 15 ]. Such same results of increased striatal glutamate in both STN and EPN stimulation cannot be explained by the same mechanism of STN and EPN stimulation.…”
Section: Discussionsupporting
confidence: 94%
“…EPN stimulation increased striatal glutamate levels in NL with DBS category and 6-HD with DBS category compared to NL category and 6-HD category, respectively. This result is in accordance with findings of other reports about increased striatal glutamate levels after STN stimulation [ 9 , 11 , 15 ]. Such same results of increased striatal glutamate in both STN and EPN stimulation cannot be explained by the same mechanism of STN and EPN stimulation.…”
Section: Discussionsupporting
confidence: 94%
“…However, we observed stable glutamate release during and after the first and fifth DBS sessions, which were below the levels observed in PD-induced animals. Interestingly, it has been shown that acute, high-frequency stimulation (as applied in DBS) induces astrocyte-mediated glutamatergic release in vitro [ 70 ], as glutamate release was observed after 20 min of STN-DBS in hemiparkinsonian rats [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Normal levels of GABA help to maintain the tightness and function of the blood-brain barrier [38]. Animal experiments have shown that the levels of GABA in the striatum of PD model are decreased, while highfrequency stimulation can signi cantly increase the levels of GABA in the striatum [39]. Clinical studies have found reduced levels of GABA are associated with visual hallucinations in PD [40].…”
Section: Discussionmentioning
confidence: 99%